1990
DOI: 10.1104/pp.93.3.1011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Endogenous Cytokinins on Reverse Mobilization in Cotyledons of Cicer arietinum L

Abstract: The embryonic axis plays an essential role in the mobilization of the main reserves of the cotyledons of seeds of Cicer arietinum L. cv Castellana. This control by the axis of the metabolism of the storage products of the cotyledons largely takes place through the cytokinins, which are transported from the embryonic axis to the cotyledons where the mobilization of reserves begins. The principal regulatory role of the endogenous cytokinins concerns the metabolism of carbohydrates and proteins; there is less inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Our results are in agreement with reports on cultivated chickpea (Munoz et al 1990;Babiano 1996, 1997;Turnbull et al 1997;Emery et al 1998;Hartung et al 2002). On the other hand, there were little different levels in hormones due to the fact that they have only studied cultivated chickpeas.…”
Section: Discussionsupporting
confidence: 96%
See 2 more Smart Citations
“…Our results are in agreement with reports on cultivated chickpea (Munoz et al 1990;Babiano 1996, 1997;Turnbull et al 1997;Emery et al 1998;Hartung et al 2002). On the other hand, there were little different levels in hormones due to the fact that they have only studied cultivated chickpeas.…”
Section: Discussionsupporting
confidence: 96%
“…He reported that IAA approximately ranged from 200 pmol g À1 fresh weight in dwarf pea genotype to 800 pmol g À1 fresh weight in slender genotypes. Munoz et al (1990) found about 200-1000 ng Z per excised cotyledon in chickpea. It was pointed out that zeatin content in buds of chickpea changed little in the first 2 h (about 20 pmol g À1 FW) after shoot decapitation, but significantly increased after 6 h (more than 35 pmol g À1 FW) (Turnbull et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current work shows that, apart from results obtained in seeds in which Z predominate over other CKs, iP and iPR were present in a majority in P. sylvestris juvenile tissues similarly to P. radiata (Valdés et al 2002, 2003, Zhang et al 2003. The occurrence of Z as the most abundant cytokinin in mature seeds of P. sylvestris was also found in P. pinea cotyledons isolated from germinating embryos (Valdés et al 2001), and it could allude to its involvement in the protein and sugar catabolism necessary for the newseedling growth, as it similarly happens in angiosperms (Muñoz et al 1990). DHZ and its riboside were hardly detectable in the same material, possibly because the process of hypocotyl thickening is under control of iP and Z-type cytokinins, but not DHZ (Lexa et al 2003).…”
mentioning
confidence: 86%
“…But, hormonal status of cultivated chickpea is little known and studies were mainly conducted on one or two normal leaf type chickpea (Munoz et al 1990;Iglesias and Babiano 1996;Turnbull et al 1997;Iglesias and Babiano 1997;Emery et al 1998;Hartung et al 2002). Davies (1995b) showed that the concentration of IAA was related to height of pea (Pisum sativum L.).…”
Section: Introductionmentioning
confidence: 98%